COCOA FARMERS CREDIT DEFAULT AND ITS IMPLICATIONS FOR RURAL AGRICULTURAL FINANCING IN GHANA - Sonny Gad ATTIPOE; Francis Kastro KAVI; Mark Kwame OFFEI; Dongqing HAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The role played by rural and community banks (RCBs) in financial intermediation in the cocoa sector is commendable, however, their full potential is not realized due to the high level of credit default by farmers. Among 95 credit takers for the 2018 to 2019 farming season, the study revealed that 68.4% of farmers defaulted, producing a loan recovery rate of 45.76% and default rate of 54.23%. The surveyed banks value the use of collateral security (47%) and fixed income guarantee (26%) as a prerequisite for accessing credit. Selected RCBs' predicaments of lending to farmers are the misappropriation of funds, high default rate, and high illiteracy rate. Averagely, farmers used 44.66% of the accessed credit amount for cocoa farming, and 55.34% on non-farm-related activities, indicating the misappropriation of funds. Defaulters’ reason for delinquency is classified into; causes due to the borrower (24.60%), causes due to the lender (32.04%), and causes due to nature (43.36%). Moreover, RCBs' perception of the causes of loan delinquency includes misappropriation of funds, unwillingness to pay, risk in cocoa farming, and high-interest rate. Finally, probit model results indicated that farmers’ repayment abilities were positively influenced by their engagement in secondary occupation, attainment of formal education, and loan terms, and negatively influenced by household size, loan amount received, interest rate, and distance to rural banks. The study recommends RCBs to enact stringent borrowing policies aimed at reducing loan delinquency among cocoa farmers in Ghana.